تطبيق تعليم اللغة الجماعة في تعليم اللغة العربية - Arif Pamessangi, Andi (Fakultas Tarbiyah dan keguruan- UIN Ar-Raniry, 2019)
The method is the theoretical basis for something important in language teaching, such as teaching Arabic. In teaching Arabic, the method has many roles, such as the steps in giving a better understanding to teachers and students about the grammar of language, its use, and other functions related to language. In this article, the author discuss about one way to teach a language, which is Community language learning. The researcher searches for the importance of Community language learning, its definition, when it originated, its goals, how the functions of the teaching elements work, as well as how they are applied to education and what have its advantages and disadvantages. Community language learning is a method developed by Charles A. Charles A. Curran and his colleagues are also called counseling learning method. Community language learning has some major characteristics. The basic principle of this method is for the teacher to act as a counselor or mentor who plays a negative or inactive role. The aim of this education is to upgrade students' competence in proficiency in the foreign language as native speakers, as well as to increase the confidence and spirit of students in using this language. Community language learning is a valid and appropriate method for Arabic Learning.